Accuracy of periapical radiographs for the diagnosis of invasive cervical resorption: an integrative review (Research, Society and Development, 2023)
Invasive cervical resorption (ICR) is a type of resorption of pathological origin that is characterized by invasion of the cervical root surface. Radiological evaluation is essential for the purposes of diagnosis, planning and implementation of treatment for ICR. Periapical radiography (PR) is the main radiographic investigation used, but it has some limitations in relation to cone beam computed tomography (CBCT). Thus, the aim of this study was to describe the accuracy of PRs for the diagnosis of ICR compared to CBCT. This is an integrative literature review. The searches were carried out in the Pubmed/MEDLINE and Scopus databases, using descriptors and their synonyms in the English language such as “root resorption”, “diagnosis”, “Cone-Beam Computed Tomography”, “Radiography, Dental”. Six articles published between 2016 and 2022 were selected for the analysis of results. Studies have shown mean values ​​of accuracy of images generated from CBCT ranging from 99% to 99.4%, sensitivity from 98.7% to 100%, specificity from 98.1% to 100%, positive predictive values ​​(PPV) from 98.1% to 100%, and negative (VPN) from 98.7% to 100%. In comparison, the mean values ​​of accuracy for diagnosing ICR based on evaluation using periapical radiographs ranged from 60% to 87.2%, sensitivity from 82.1% to 86%, specificity from 89% to 93.2%, PPV from 48.5% to 91.4% and VPN from 49.4% to 83.7%. PRs are significantly less accurate than CBCT for diagnosing ICR, since anatomical alteration, geometric compression and possible overlapping of anatomical structures that can obscure the area of ​​interest.